2020
DOI: 10.1002/joa3.12361
|View full text |Cite
|
Sign up to set email alerts
|

Diverse activation patterns during persistent atrial fibrillation by noncontact charge‐density mapping of human atrium

Abstract: Background Global simultaneous recording of atrial activation during atrial fibrillation (AF) can elucidate underlying mechanisms contributing to AF maintenance. A better understanding of these mechanisms may allow for an individualized ablation strategy to treat persistent AF. The study aims to characterize left atrial endocardial activation patterns during AF using noncontact charge‐density mapping. Methods Twenty‐five patients with persistent AF were studied. Activation patterns were characterized into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…During the UNCOVER post-market clinical study [17], distinct LCC patterns, as previously described by Chi et al [9] in PsAF, were observed and categorized in all 129 subjects. To the best of our knowledge, the relationship between these LCC pattern-cores and LVAs identified by BVM had not been investigated previously.…”
Section: Localized Complex Conduction Patterns and Lowvoltage Areasmentioning
confidence: 66%
See 2 more Smart Citations
“…During the UNCOVER post-market clinical study [17], distinct LCC patterns, as previously described by Chi et al [9] in PsAF, were observed and categorized in all 129 subjects. To the best of our knowledge, the relationship between these LCC pattern-cores and LVAs identified by BVM had not been investigated previously.…”
Section: Localized Complex Conduction Patterns and Lowvoltage Areasmentioning
confidence: 66%
“…Activation maps of PsAF were acquired by AcM, previously described in detail by Shi et al [9]. In summary, AcM provides maps of electrical activation across an ultrasoundacquired cardiac chamber surface.…”
Section: Charge Density Global Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…AcQMap also described a new repetitive pattern which is an attempt to spatially localize fibrillatory conduction called localized irregular activation (LIA). In recent studies, this has been subdivided into four potentially underlying mechanisms based on propagation patterns (Figure 1) 7 . However much work needs to be done to better translate these studies into useful targets for additional ablation beyond the pulmonary veins.…”
mentioning
confidence: 99%
“…A preliminary study demonstrated that the dipole density (unit, μCoulombs/cm) represents an actual biophysics of cardiac activity that is sharper and narrower than the voltage, so that it can provide a more discrete wavefront propagation 4 . In this issue of the Journal , Rui Shi et al retrospectively analyzed and characterized activation patterns of persistent AF using this system 5 . The main findings described in this paper were as follows: (a) Persistent AF is characterized by highly dynamic and heterogeneous activation patterns consisting of localized irregular activation (LIA) (63%), localized rotational activation (LRA) (20%), and focal with centrifugal activation (FCA) patterns (17%); (b) a combination of slow/accelerated conduction, pivotal activation, and collisions were observed; (c) preferential conduction areas with repetitive LRA and LIA were detected in the mid‐anterior (48%) and lower‐posterior (40%) LA wall; and (d) observations of transitions between LIA and LRA with merging and breaking of wavefronts were noted.…”
mentioning
confidence: 99%